Performance of primary healthcare dentists in a distance learning course in pediatric dentistry. (September 2019) - Bavaresco, Caren Serra; Bragança, Silvana; Vencato, Vithória; Feltes, Brenda; Sória, Giordano Santana; Brew, Myrian Camara; de Moura, Flávio Renato; D'Ávila, Otávio Pereira; Umpierre, Roberto Nunes; Harzheim, Erno; Rodrigues, Jonas Almeida
Abstract: Objective: Children are an important portion of the population of the territories covered by Primary Health Care (PHC), with needs and characteristics that can be managed at this level of care. Therefore, it is essential that professionals working in PHC be capable of providing child care. The aim of this study was to evaluate the performance of dentists working in primary healthcare (PHC) in a pediatric dentistry distance learning (DL) course, and to investigate the relationship between the grades earned on questionnaires applied after each course module and features of their personal and professional profile. Method: The study used a convenience sample of 201 dentists working in PHC, who enrolled in a DL course offered by a telehealth center in the state of Rio Grande do Sul, Brazil. The course consisted of video classes on restorative dentistry, endodontics, dental trauma, and clinical management in pediatric dentistry. After completing each module, each participant was asked to answer a questionnaire to assess their acquisition of immediate knowledge. Student's t -test and the ANOVA test were used to assess the relationship between the mean grade earned and the variables of sex, age, type of training institution, time since graduation, and years working in PHC. Results: A significant relationship was observed between type of training institution (public) and the grade earned on the restorative dentistry questionnaire, and also between time since graduation and the grade earned on the dental trauma questionnaire (p < 0.05). No relationship was observed between the personal/professional variables and the grades earned on the endodontics and clinical management questionnaires. Grades were significantly lower on the endodontics questionnaire (p < 0.05). Discussion: The large number of dentists enrolled in this DL course is a demonstration that there is great interest in pediatric dentistry contents. Improvement of DL courses may lead to the enhancement of professionals and their skills, and to a significant improvement in the quality of care provided to children in public health networks. Conclusion: It was concluded that training in a public institution and a longer time since graduation positively influenced the grades earned on the restorative dentistry and dental trauma questionnaires, respectively.